2021
DOI: 10.1101/2021.03.22.435145
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide identification of the oatMLOfamily and identification of a candidateAsMLOassociated with powdery mildew susceptibility

Abstract: Blumeria graminis f. spp. avenae, is the causal agent of powdery mildew disease in oats (Avena sativa). It is the most significant limiting factor to oat production, with yield losses ranging from 5%-40%, during high disease pressure conditions. Certain members of the Mildew Locus O (MLO) gene family have been shown to act as powdery mildew susceptibility factors in many different plant species. A loss-of-function mutation of specific MLO genes confers broad-spectrum resistance against powdery mildew pathogens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…MLO is a powdery mildew susceptibility gene that was initially identified in barley but that is broadly conserved across plant species (Appiano et al, 2015; Jørgensen, 1992). In oats, several MLO-like genes have been identified based on sequence homologies (Reilly et al, 2021), but their functionality has not been shown yet. Taken together, even though several intriguing putative functions of Pm13 have been identified, they remain speculative and additional efforts are necessary to fine map and clone Pm13.…”
Section: Discussionmentioning
confidence: 99%
“…MLO is a powdery mildew susceptibility gene that was initially identified in barley but that is broadly conserved across plant species (Appiano et al, 2015; Jørgensen, 1992). In oats, several MLO-like genes have been identified based on sequence homologies (Reilly et al, 2021), but their functionality has not been shown yet. Taken together, even though several intriguing putative functions of Pm13 have been identified, they remain speculative and additional efforts are necessary to fine map and clone Pm13.…”
Section: Discussionmentioning
confidence: 99%
“…EF1α was used as a reference gene for eggplant and petunia [51,52]. Tubulin was used as a reference gene for studying the mulberry [53], and 28SrRNA was used as a reference gene for studying the oat [54]. The reference genes used to investigate the functional gene expression profiles associated with tomato PM are also different.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes do not share arrangements with any other known GPCR. The 7TM domain structure has been biochemically confirmed for one MLO from oat (Reilly et al, 2021). Researches told that Arabidopsis consists of only one canonical GTP gene i.e.…”
Section: Genes For Gtp-protein-signalling In Plant Genomementioning
confidence: 91%
“…GTP-binding activities and substrates for ADP ribosylation catalyzed by pertussis toxin were detected in gel filtration fractions of extracts from pea (Pisum sativum) and Lemna paucicostata (Schneider et al, 2005). A filter assay has been used to uncover small GTP binding proteins in the green alga (Sasaki and Burr, 2000), in microsomes of zucchini (Cucurbita pepo) hypocotyl (Reilly et al, 2021), in chloroplast outer envelope membrane and nuclear envelope from pea (Youssefian et al, 1993a). In 2015, in the cytosol of pea plumule cells ARF-like protein was discovered by Rout and Panigrahi.…”
Section: Detection Of Gtp-binding Proteinsmentioning
confidence: 99%